Elastic Properties of Liquid Surfaces Coated with Colloidal Particles. (31st May 2015) - Bormashenko, Edward; Whyman, Gene; Gendelman, Oleg
Abstract : The physical mechanism of elasticity of liquid surfaces coated with colloidal particles is proposed. It is suggested that particles are separated by water clearings and the capillary interaction between them is negligible. The case is treated when the colloidal layer is deformed normally to its surface. The elasticity arises as an interfacial effect. The effective Young modulus of a surface depends on the interfacial tension, equilibrium contact angle, radius of colloidal particles, and their surface density. For the nanometrically scaled particles the line tension becomes essential and has an influence on the effective Young modulus.